Analysis and Design of a Rooftop Photovoltaic (PV) System in Bulaksumur, Yogyakarta Using Archelios Pro - Gheri Febri Ananda; Kukuh Bintoro; Asdaqul Khair (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
This research focuses on the design and analysis of a rooftop photovoltaic (PV) system in Bulaksumur, Yogyakarta, using the Archelios Pro software. The objective of the study is to evaluate the efficiency and effectiveness of the PV system in terms of energy production and cost savings. The methods used include simulation and analysis with Archelios Pro, which allows for accurate modeling and estimation of energy production. The load profile at the research site was analyzed to determine the annual energy consumption, which reached 8,859 kWh. The designed PV system consists of 15 modules with a total capacity of 6.60 kWp. The results show that the PV system, without battery storage, produces an annual energy output of 10,185 kWh, meeting 115% of the household's annual energy needs. However, without battery storage, only 25.8% of the generated energy is directly usable. In the scenario with battery storage, self-consumption increases from 25.8% to 45.8%, and reliance on the electricity grid decreases from 5,510 hours to 4,179 hours per year. Economic analysis reveals annual cost savings of Rp 3,847,926, although the payback period exceeds 20 years. The use of the PV system also reduces annual carbon emissions by 3,965.25 kg of CO‚‚, contributing to efforts to achieve net-zero emissions in Indonesia.